Pengaruh Komunikasi dan Motivasi Kerja Kepemimpinan Kepala Sekolah Terhadap Kinerja Tenaga Pendidik, di MA Matholi’ul Anwar Kabupaten Lamongan - Muhammad Siroj Hakim; Misbahus Surur (Program Studi Manajemen Pendidikan Islam, 2020)
This study aims to determine the effect of school principal, communication, and work motivation on MA Matholi'ul Anwar Sungelebak Karanggenang teachers in Lamongan Regency. This research is a type of qualitative research using a case study approach to understand the phenomena about what is experienced by research subjects. analysis using interpretative descriptive research, the researcher conducts research based on literature literature and observations in the field, namely through observation and interviews with research objects, as the main method. The results in this study indicate that leadership, communication, and work motivation affect the performance of MA Matholi'ul Anwar Sungelebak Karanggenang teachers in Lamongan Regency. partially the most influential is leadership on the performance of teaching staff communication and work motivation.